La colonna sonora come mixtape: Rap italiano e cinema agli albori degli anni Duemila (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
This essay focuses on the first convergence between Italian rap and cinema that took place between the late 1990s and the first years of the 21st century. The soundtrack of three films that bear witness of such a process, “Torino Boys” (1997, by Antonio and Marco Manetti), “Semiautomatico” (1999, by AJ Sikabonyi), and “Zora la vampira” (2000, by Antonio and Marco Manetti), will be scrutinized in details. The scope of the analysis is to offer a reading of these films on the background of the specific creative practices of hip hop culture.